Social Innovation in Sustainable Urban Development (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
How can a city advance from social invention to social innovation, to attain sustainable urban development (SUD)? Many new ideas, initiatives, and showcases for social innovation have been introduced; however, project-based forms of experimentation are often just part of the ongoing urban politics (or governmentality), and consequently somewhat ephemeral, with traditional siloed city administrations remaining a central obstacle to SUD. Our Special Issue presents twelve papers that address the question of social innovation in sustainable urban development from very different angles. The contributions span issues concerning smart cities, innovation in the adaptive reuse of urban heritage, as well as policy options for regions in transition. In terms of social innovation for SUD purposes, the presented solutions range from transferable legal formalizations to the creation of urban ecosystems whose institutional structures ensure the inclusion of the civil society. Instead of a comprehensive, integrative SUD, robust sectoral solutions, or even phased solutions, are more likely to be sought.